Pengaruh Energi Terbarukan Terhadap Kualitas Lingkungan di Negara ASEAN - Amelia Fitri; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to determine the extent of the impact of renewable energy on environmental quality in ASEAN countries. This study uses secondary data sourced from the World Bank from 1990 to 2023 with research variables grouped into three parts, namely the dependent variable, which in this study is defined as environmental quality, and independent variables, namely renewable energy, as well as control variables used in this study, namely economic openness, urbanization, foreign direct investment (FDI), gross domestic product (GDP), and forest area. This study uses panel data regression analysis with a cross section of 7 countries in ASEAN and a time series from 1990 to 2023. The results show that renewable energy has a positif effect on environmental quality, as measured by carbon dioxide (CO2) emission levels. Therefore, it has the potential to reduce CO2 emission levels in ASEAN countries.